THE POWER OF CHILD WITNESSES AS EVIDENCE IN CRIMINAL CASE CASES - Gunawan, Wahyu Indra; Makarao, M Taofik; Harahap, Hapendi (Jurnal Hukum Jurisdictie, 2023)
Witness testimony is an important factor in all judicial process implementation activities and as evidence that can incriminate or relieve the defendant. Article 1 point 1 of Law Number 13 of 2006 concerning Protection of Witnesses and Victims, states "Witnesses are people who can provide information in the interests of investigations, investigations, prosecutions, and examinations at court hearings regarding a criminal case that he himself heard, saw himself, and/or he experienced it himself. Article 1 number 29 of the Criminal Procedure Code explains that: "A child's statement is information given by a child about things that are needed to clarify a criminal case for the purposes of examination in matters and according to the method stipulated in this law. The right of children to testify in court is protected by law. As regulated in Article 12 of the Convention on the Rights of the Child which has been ratified by Indonesia with Presidential Decree No. 36 of 1990